Kim's Convenience : the complete series [videorecording (DVD)] - Choi, Ins, 1974-; Choi, Ins, 1974-; Choi, Ins, 1974-; White, Kevin (Screenwriter); Fecan, Ivan, 1954-; Lee, Paul Sun-Hyung, 1972-; Yoon, Jean, 1962-; Liu, Simu, 1989-; Bang, Andrea; Phung, Andrew; Power, Nicole (Universal Pictures Home Entertainment, 2022)
"Kim's Convenience is the funny, heartfelt story of The Kims--a Korean Canadian family running a convenience store in downtown Toronto. Based on the hit play by Ins Choi, this acclaimed comedy explores the multicultural community and the generational tension between immigrant parents and their Canadian-born children with smart comedy and authentic depth.The series is set in urban Regent Park, a rundown neighborhood bustling with immigrants and rich in cultural diversity, at the heart of which is the Kim family and their store, and the series finds laughter in the trials of running a literal "Mom and Pop" shop while raising kids in a culture that is not quite your own."--back of case.